Endovascular thrombectomy is cost-saving in patients with acute ischemic stroke with large infarct - Schwarting, Julian; Froelich, Matthias F.; Kirschke, Jan S.; Mehrens, Dirk; Bodden, Jannis; Sepp, Dominik; Reis, Jonas; Dimitriadis, Konstantinos; Ricke, Jens; Zimmer, Claus; Boeckh-Behrens, Tobias; Kunz, Wolfgang G. (Frontiers in Neurology, 2024)
Objective: Endovascular thrombectomy (EVT) is the standard of care for acute large vessel occlusion stroke. Recently, the ANGEL-ASPECT and SELECT 2 trials showed improved outcomes in patients with acute Ischemic Stroke presenting with large infarcts. The cost-effectiveness of EVT for this subpopulation of stroke patients has only been calculated using data from the previously published RESCUE-Japan LIMIT trial. It is, therefore, limited in its generalizability to an international population. With this study we primarily simulated patient-level costs to analyze the economic potential of EVT for patients with large ischemic stroke from a public health payer perspective based on the recently published data and secondarily identified determinants of cost-effectiveness. Methods: Costs and outcome of patients treated with EVT or only with the best medical care based on the recent prospective clinical trials ANGEL-ASPECT, SELECT2 and RESCUE-Japan LIMIT. A A Markov model was developed using treamtment outcomes derived from the most recent available literature. Deterministic and probabilistic sensitivity analyses addressed uncertainty. Results: Endovascular treatment resulted in an incremental gain of 1.32 QALYs per procedure with cost savings of $17,318 per patient. Lifetime costs resulted to be most sensitive to the costs of the endovascular procedure. Conclusions: EVT is a cost-saving (i.e., dominant) strategy for patients presenting with large ischemic cores defined by inclusion criteria of the recently published ANGEL-ASPECT, SELECT2, and RESCUE-Japan LIMIT trials in comparison to best medical care in our simulation. Prospective data of individual patients need to be collected to validate these results